2020
DOI: 10.1128/jb.00444-19
|View full text |Cite
|
Sign up to set email alerts
|

RelZ-Mediated Stress Response in Mycobacterium smegmatis : pGpp Synthesis and Its Regulation

Abstract: Stringent response is a conserved stress response mechanism in which bacteria employ the second messengers guanosine tetraphosphate and guanosine pentaphosphate [collectively termed (p)ppGpp] to reprogram their cellular processes under stress. In mycobacteria, these alarmones govern a multitude of cellular phenotypes, such as cell division, biofilm formation, antibiotic tolerance, and long-term survival. Mycobacterium smegmatis possesses the bifunctional RelMsm as a (p)ppGpp synthetase and hydrolase. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 46 publications
3
61
0
Order By: Relevance
“…Another understudied aspect of (p)ppGpp regulation is whether ppGpp and pppGpp, while commonly referred to and characterized as a single species, target the same or different cellular pathways 21 . In addition, there is evidence for potential existence of a third alarmone, guanosine-5′-monophosphate-3′-diphosphate (pGpp), since several small alarmone synthetases can synthesize pGpp in vitro 22 , 23 . However, the clear demonstration of pGpp in bacterial cells has been challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Another understudied aspect of (p)ppGpp regulation is whether ppGpp and pppGpp, while commonly referred to and characterized as a single species, target the same or different cellular pathways 21 . In addition, there is evidence for potential existence of a third alarmone, guanosine-5′-monophosphate-3′-diphosphate (pGpp), since several small alarmone synthetases can synthesize pGpp in vitro 22 , 23 . However, the clear demonstration of pGpp in bacterial cells has been challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Any R-loops formed are removed by the RNase HII and (p)ppGpp helps to destabilize the stalled RNA polymerase via an unknown mechanism to rescue the cells from replication stress ( Krishnan et al, 2016 ). In addition, RelZ mediates antibiotic tolerance in M. smegmatis but does not impact biofilm formation significantly ( Petchiappan et al, 2020 ).…”
Section: Relz (Ms_rhii-rsd)mentioning
confidence: 99%
“…The synthetic subdomain of RelZ is a tetramer in solution like the other solved structures of RelP and RelQ ( Steinchen et al, 2015 , 2018 , 2020 ; Steinchen and Bange, 2016 ). Petchiappan et al (2020) showed that RelZ prefers guanosine monophosphate (GMP) as a substrate and synthesizes pGpp. To understand the difference between pGpp and ppGp, the reaction mixture was treated with NaOH that hydrolyzes only pGpp.…”
Section: Relz (Ms_rhii-rsd)mentioning
confidence: 99%
See 2 more Smart Citations